THE GRAPHING SKILL OF LINE EQUATION AND QUADRATE EQUATION AT THE FIRST YEAR STUDENTS - Zulfaneti, Zulfaneti; Edriati, Sofia; Mukhni, Mukhni (Universitas PGRI Sumatera Barat, 2018)
The drawing a graph of the equation is positioned by it as the material prerequisites that must be mastered to solve the problems on the subject. However, based on teaching experience for many students who indicated not been able to describe the graph equation graph. The study aims to describe the students' ability to draw graphs of quadratic and line equations,of first-year students who took Calculus subject at Mathematics Department, Padang, Indonesia. The data source was selected purposive and snowball sampling. Sources of data in this study were 70 first year students in Differential Calculus subject class. Research shows that understanding of students to graph a quadratic equation is still very low, they often mixed graphs of quadratic equations and linear equations, and understanding of students to graph line equation is still very low, especially on understanding the line y = k and x = k, k is a number